Electrical, Information Engineering and Mechatronics 2011 Proceedings of the 2011 International Conference on Electrical, Information Engineering and Mechatronics (EIEM 2011) - Wang, Xudong; Wang, Fuzhong; Zhong, Shaobo; SpringerLink (Online service) (London : Springer London, 2012)
As future generation electrical, information engineering and mechatronics become specialized and fragmented, it is easy to lose sight of the fact that many topics in these areas have common threads and, because of this, advances in one discipline may be transmitted to others. The 2011 International Conference on Electrical, Information Engineering and Mechatronics (EIEM 2011) is the first conference that attempts to follow the above idea of hybridization in electrical, information engineering, mechatronics and applications. This Proceedings of the 2011 International Conference on Electrical, Information Engineering and Mechatronics provides a forum for engineers and scientists to address the most innovative research and development including technical challenges and social, legal, political, and economic issues, and to present and discuss their ideas, results, works in progress and experience on all aspects of electrical, information engineering, mechatronics and applications. Engineers and scientists in academia, industry, and government will find a insights into the solutions that combine ideas from multiple disciplines in order to achieve something more significant than the sum of the individual parts in all aspects of electrical, information engineering, mechatronics and applications.
Keywords: Engineering; Computer engineering; Engineering; Electrical Engineering; Mechatronics